Rancangan Penyuluhan untuk Mengubah Persepsi Petani Ubi Jalar Terhadap Pengendalian Hama Lanas Menggunakan Daun Mimba dan Feromon - Desandi A.M. Ramadhiana; Rudi Hartono; Nazaruddin (Politeknik Pembangunan Pertanian Bogor, 2022)
One of the obstacles in the sweet potato production system is the attack of the sweet potato weevil (Cylas Formicarius) that is the main pest on sweet potato plants. The efforts of farmers in Maja District to deal with these pests are still low and depend on the use of chemical pesticides. The behaviour of farmers is influenced by the perception of farmers who consider chemical pesticides to be the main solution in controlling plant-disturbing organisms. Innovations in pest control can be carried out with preventive measures such as the use of pheromone that trap and disrupt pest mating and plant-based insecticides that are more environmentally friendly. The study aims to analyze the perception of sweet potato farmers on controlling sweet potato weevil pests through the use of pheromones and neem leaf vegetable insecticides, related factors and strategies that can be done in increasing farmers' perceptions. The results of descriptive analysis of 72 sample respondents can be seen that the perception of sweet potato farmers in Maja District on the use of pheromones and neem leaf vegetable insecticides in controlling sweet potato weevil pests is in the poor category with a value of 49.9%. The results of the correlation analysis of rank spearman at a significance level of 5% (0.05) show related factors including land area, income, technical aspects and social interaction.